2020
DOI: 10.1111/jvim.15700
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cerebellomedullary and lumbar cerebrospinal fluid analysis in dogs with neurological disease

Abstract: Background Cerebrospinal fluid (CSF) analysis aids in categorizing underlying disease processes in patients with neurologic disease. Convention suggests that CSF should be collected caudal to the lesion. However, little evidence exists to justify this assertion. Hypothesis/Objectives Evaluate the clinicopathologic differences between CSF collected from the cerebellomedullary (CM) and lumbar cisterns in dogs presented for evaluation of neurologic disease. Animals Fifty‐one client‐owned dogs undergoing magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 11 publications
2
20
2
Order By: Relevance
“…A comparison of paired CSF samples collected from CM and lumbar cisternae in neurologic dogs revealed that in patients with thoracolumbar myelopathies, CSF from the lumbar cisterna was significantly more likely to yield an abnormal result 10 . These findings agree with another study that evaluated CSF‐CK concentrations in samples collected from CM and lumbar cisternae in dogs with thoracolumbar IVDD 17 .…”
Section: Brief Communicationsupporting
confidence: 83%
See 2 more Smart Citations
“…A comparison of paired CSF samples collected from CM and lumbar cisternae in neurologic dogs revealed that in patients with thoracolumbar myelopathies, CSF from the lumbar cisterna was significantly more likely to yield an abnormal result 10 . These findings agree with another study that evaluated CSF‐CK concentrations in samples collected from CM and lumbar cisternae in dogs with thoracolumbar IVDD 17 .…”
Section: Brief Communicationsupporting
confidence: 83%
“…However, in the clinical setting, the selection of sites for collection are often influenced by other factors, such as preference and experience of the clinician, patient safety, or body conformation 8 . A comparison of CSF analytes collected from both the CM and lumbar cisterna has indicated that in patients with lesions localizing to the thoracolumbar spine, CSF from the CM cisterna is likely to yield false‐negative results 10 . However, multiple studies evaluating biomarkers in CSF as prognostic factors in dogs with thoracolumbar disease only evaluated CSF from the CM cisterna 2,11‐13 .…”
Section: Brief Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have highlighted the potential clinical benefit of collecting both CMC and LSS CSF samples. [24][25][26] More specifically, Carletti et al 24 studied a population of 111 dogs diagnosed with SRMA with paired CSF samples (CMC and LSS). In eight of 111 patients, only one of the two samples had an increased TNCC.…”
Section: Discussionmentioning
confidence: 99%
“…A discrepancy on the clinicopathological conclusion between the two samples was observed in one case, where only the CMC sample was diagnostic of SRMA. Recent studies have highlighted the potential clinical benefit of collecting both CMC and LSS CSF samples 24–26 . More specifically, Carletti et al 24 studied a population of 111 dogs diagnosed with SRMA with paired CSF samples (CMC and LSS).…”
Section: Discussionmentioning
confidence: 99%